Przyjaźń podług Lucjusza Anneusza Seneki. Kilka spostrzeżeń - Wesołowska, Elżbieta (Wydawnictwo "Poznańskie Studia Polonistyczne" oraz Wydawnictwo PTPN, 2010)
This article attempts to examine the problem of friendship as it was understood by Seneca in his letters sent to Lucillus. The author scrutinizes the main items in the philosopher's autobiography to investigate the influence of the events from Seneca's biography in the shaping of the opinions of the thinker. Lucillus, the addressee of the letters, was actually Seneca's long-time friend and confidant. The issue of friendship has a long and rich tradition of its own in the antique times. This particular relationship between human beings was of much interest to Plato, Aristotle, Epicurus, Cicero and many others. Seneca does not venture into an attempt at creating a vision for coherent science related to friendship. What he does though is to furnish a vast array of thoughts concerning such questions as: who is worthy of friendship, why is it worth having a friend and what forms the basis for friendship? Strangely enough, these establishments made by Seneca somehow seem to be more close to us than those in which the philosopher constructs the image of a superhuman wise man, a stoic.
Friendship according to Lucius Annaeus Seneca. A handful of core defining observations
Keywords: Seneka Lucjusz Anneusz; Przyjaźń; Listy moralne; Lucyliusz